Sodio y enfermedad cardiovascular: contexto en Latinoamérica (2015)
ABSTRACT: Cardiovascular diseases (CVD) are the main causes of morbidity and mortality in Latin America (LA). A high sodium intake is one of main risk factors for CVD. Strategies aiming to decrease sodium intake has been shown health benefits as reduction of blood pressure, and incidence of CVD at the population level. Data of salt/sodium intake in most LA countries is not up dated and it has been estimated by different methodologies. Nevertheless, it is highly possible that current salt/sodium intake in LA exceeds recommended goals from international organizations. Argentina, Brazil, Chile, Cuba, Colombia, Costa Rica, Uruguay, México Venezuela and Paraguay have implemented strategies to reduce salt/sodium intake at population level; as has been recommended by Pan American Health Organization (PAHO) recommend. The, aim of this review was to identify epidemiologic evidence behind sodium reduction strategy to reduce and prevent CVD. Additionally, this review intended to describe main implemented actions in LA.